Diferença salarial de gênero e raça no mercado de aplicativo de entregas - Rodrigues, Gabriella Nunes Cordeiro (2022)
This study analyzes wage differences both by gender and by race in a delivery app. We examined 133,856 workers observed both in the delivery platform databases and in the traditional formal labor market. It was observed that in the traditional formal jobs, there is a significant gender and racial wage gap, with women and blacks with lower earnings than men and white workers with equivalent observable characteristics. On the delivery platform, lower average earnings were also observed for women. However, the gap was smaller, and it can be explained by variables associated with productivity and efficiency that differ between male and female drivers, such as the use of motorcycles and turnover levels. However, the same gap reduction could not be verified for black workers.